Obstetric and Perinatal Characteristics of Teenage Pregnancies: an Analysis of Five Year Period in dr. Cipto Mangunkusumo Hospital, Jakarta - Junita Indarti; David Eka Prasetya; Hari Sandi; Imam Rahmadi; Raymond Surya (Faculty of Medicine Universitas Indonesia, 2021)
Abstract Teenage pregnancy leads to higher rates of maternal and perinatal complication and has been amajor challenge globally. This study aims to evaluate the obstetric and perinatal characteristics of teenagepregnancies in Indonesian population. A cross-sectional study through medical records was performed attertiary cared dr. Cipto Mangunkusumo Hospital, Jakarta, from 2014 to 2018. We recruited average maternalage of women and teenagers who carried singleton live pregnancies and delivered at tertiary care. Obstetricalcomplications include anemia at labor, preeclampsia/eclampsia, postpartum hemorrhage, preterm rupture ofmembrane, induction of labor, cesarean section delivery and perinatal outcomes include small-for-gestationalage, stillbirth, intrauterine growth restriction, preterm birth, low birth weight, 5th minimum APGAR score wereassessed. Statistical analysis was done using SPSS 20. There were 4265 eligible subjects during 5-yearperiod. The prevalence of teenage pregnancy (11-19 years old) was 543/4265 (12.7%). Teenage pregnancyhad a higher incidence of preterm deliveries (OR 2.047, 95%CI 1.660–2.524, p<0.001) and anemia at labor(OR 1.433, 95%CI 1.113-1.843, p=0.005). Low birth weight babies (OR 1.520, 95%CI 1.229–1.879, p<0.01)were associated with teenage pregnancy. Teenage pregnancy contributes to higher incidence of pretermdeliveries, anemia at labor, and low birth weight. Keywords: teenage, pregnancy, outcome, maternal, perinatal. Karakteristik Obstetrik dan Perinatal pada Kehamilan Remaja: Analisis Lima Tahun di RSUPN Dr. Cipto Mangunkusumo, Jakarta Abstrak Kehamilan remaja meningkatkan komplikasi maternal dan perinatal serta merupakan tantangan global.Studi ini bertujuan untuk mengevaluasi karakteristik obstetrik dan perinatal kehamilan remaja di Indonesia.Studi potong lintang melalui rekam medis dilakukan di RSCM, Jakarta, pada tahun 2014 hingga 2018. Kriteriainklusi ialah kehamilan remaja dan usia reproduksi pasien yang melahirkan di RSCM. Komplikasi obstetrikyang dinilai adalah anemia saat persalinan, preeklamsia/eklamsia, perdarahan pascasalin, ketuban pecahdini, induksi persalinan, seksio sesarea, dan luaran perinatal yaitu janin kecil, lahir mati, pertumbuhan janinterhambat, persalinan prematur, berat lahir rendah, dan skor APGAR 5 menit. Analisis statistik menggunakanSPSS 20. Terdapat 4265 subjek selama 5 tahun dengan prevalensi kehamilan remaja (11-19 tahun) 543/4265(12,7%). Kehamilan remaja meningkatkan insidens persalinan prematur yang lebih tinggi (OR 2,047, 95%CI1,660–2,524, p<0,001) dan anemia saat persalinan (OR 1,433, 95%CI 1,113-1,843, p=0,005). Berat badan lahirrendah berhubungan dengan kehamilan remaja (OR 1,520, 95%CI 1,229–1,879, p<0,01). Kehamilan remajamemiliki dampak lebih tinggi terhadap persalinan prematur, anemia saat persalinan, dan berat lahir rendah. Kata kunci: remaja, kehamilan, luaran, maternal, perinatal.